PREVALENCE OF CYTOMEGALOVIRUS ANTIBODY IN THAI-NORTHEASTERN BLOOD DONORS - Urwijitaroon, Yupa; Teawpatanataworn, Sataporn; Kitjareontharm, Anong (ศรีนครินทร์เวชสาร, 2013)
The prevalence of cytomegalovirus antibody was studied in sera of 359 Northeastern blood donors with an age range of 17-59 years by ELISA for anti-CMV total antibody (anti-CMV). Anti-CMV was detected in 93.31% (335/359) of blood donors. The prevalence in males was 91.53% (227 in 248) while female donors showed 97.30% (108 in 111) positive for anti-CMV. The result demonstrated no statistically significant difference according to sex or age. One-hundred and eighty serum samples with positive anti-CMV were reexamined for anti-CMV IgM antibody. Only one sample was found to be positive. This study suggested that CMV seronegative blood supply was very limitted. Therefore leucocyte-depleted blood should be the method of choice for prevention of post-transfusion CMV infections in high risk recipients.